Pemanfaatan Selulosa Bakteri sebagai Bahan Baku Pembuatan Kertas Ramah Lingkungan - Swara, Debbie Paras; Harunsyah, Harunsyah; Fachraniah, Fachraniah (Politeknik Negeri Lhokseumawe, 2024)
The use of of cellulose from wood is growing every year in Indonesia. Continuous environmental harm results from this. In this study, paper was made using bacterial cellulose activator, tapioca flour, and coconut water as basic materials to make it more environmentally friendly. In this study, the impact of bacterial cellulose mass and tapioca flour mass on the final paper was examined. The amounts of 100, 125, 150, 175, and 200 g of bacterial cellulose and 5, 10, 15, 20, and 25 g of tapioca flour were the variables employed in this study. Additionally, the finished paper is tested for gramage, tensile strength, water content, functional group (FTIR), and a SEM test. According to the grammage test results, combinations of 100 g of bacterial cellulose and 25 g of tapioca flour had a higher grammage value than the others, 75 g/m2. The mass variation of 100 g bacterial cellulose with a mass of 25 g tapioca flour had the highest value in the tensile strength test, with a value of 0.808803 Mpa. In contrast, the mass variation of 100 g bacterial cellulose with a mass of 25 g tapioca flour had the greatest value in the water content test with a value of 5.91%.